Алгоритм користувацького запиту в архівних інформаційно-пошукових системах - Вовк, Наталія (Видавництво Львівської політехніки, 2018)
The author of the article considers the key issues of archival search – users inquiries. The archive is presented as an information retrieval system. The author demonstrates algorithms for selecting an archive and responding to a user's request.
Keywords: архів; запит; інформаційно-пошукова система; пошук; користувачі; інформаційна потреба